Nitrate supplementation`s improvement of 10-km time-trial performance in trained cyclists - Cermak, N. M.; Gibala, M. J.; van Loon, L. J. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Six days of dietary nitrate supplementation in the form of beetroot juice (~0.5 L/d) has been reported to reduce pulmonary oxygen uptake (VO2) during submaximal exercise and increase tolerance of high-intensity work rates, suggesting that nitrate can be a potent ergogenic aid. Limited data are available regarding the effect of nitrate ingestion on athletic performance, and no study has investigated the potential ergogenic effects of a small-volume, concentrated dose of beetroot juice. The authors tested the hypothesis that 6 d of nitrate ingestion would improve time-trial performance in trained cyclists. Using a double-blind, repeated-measures crossover design, 12 male cyclists (31 ± 3 yr, VO2peak = 58 ± 2 ml · kg-1 · min-1, maximal power [Wmax] = 342 ± 10 W) ingested 140 ml/d of concentrated beetroot (~8 mmol/d nitrate) juice (BEET) or a placebo (nitrate-depleted beetroot juice; PLAC) for 6 d, separated by a 14-d washout. After supplementation on Day 6, subjects performed 60 min of submaximal cycling (2 × 30 min at 45% and 65% Wmax, respectively), followed by a 10-km time trial. Time-trial performance (953 ± 18 vs. 965 ± 18 s, p < .005) and power output (294 ± 12 vs. 288 ± 12 W, p < .05) improved after BEET compared with PLAC supplementation. Submaximal VO2 was lower after BEET (45% Wmax = 1.92 ± 0.06 vs. 2.02 ± 0.09 L/min, 65% Wmax 2.94 ± 0.12 vs. 3.11 ± 0.12 L/min) than with PLAC (main effect, p < .05). Wholebody fuel selection and plasma lactate, glucose, and insulin concentrations did not differ between treatments. Six days of nitrate supplementation reduced VO2 during submaximal exercise and improved time-trial performance in trained cyclists.